REPRESENTAÇÕES CULTURAIS E PUBLICIZAÇÃO DA VIDA SOCIAL NA LITERATURA LATINA: A MULHER E O AMOR NO "CORPUS OVIDIANUM" - Cabeceiras, Manuel Rolph de Viveiros (PHOÎNIX, 2020)
The purpose of this paper is to relate a thematic research around love and woman in Ovid´s work with the concept of "publicization of social life" developped by Jean-Pierre Vernant:s and Chortler cultural history.